Inside Britain's MI6 : Military Intelligence 6 - McCormack, Shaun (New York : Rosen Pub. Group, 2003)
Presents Britain's Military Intelligence 6 (MI6) as newly focused against terrorist networks throughout the world.
Includes bibliographical references (p. [60]-61) and index.
Keywords: Great Britain. -- MI6 -- History -- Juvenile literature; Great Britain. -- MI6.; Intelligence service -- Great Britain; Espionage, British